2022
DOI: 10.3390/en15093105
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Daily Electricity Consumption in Thailand Using Regression, Artificial Neural Network, Support Vector Machine, and Hybrid Models

Abstract: This article involves forecasting daily electricity consumption in Thailand. Electricity consumption data are provided by the Electricity Generating Authority of Thailand, the leading power utility state enterprise under the Ministry of Energy. Five forecasting techniques, including multiple linear regression, artificial neural network (ANN), support vector machine, hybrid models, and ensemble models, are implemented. The article proposes a hyperparameter tuning technique, called sequential grid search, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…The comparative performance between the proposed model and prior studies is shown in Table 11. This comparative analysis is conducted with the other models that appear in the literature such as benchmark model 1 [53], LSTM [88], XGBoost [89], and SVM [90]. All comparative models follow the same structure, as outlined in prior research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The comparative performance between the proposed model and prior studies is shown in Table 11. This comparative analysis is conducted with the other models that appear in the literature such as benchmark model 1 [53], LSTM [88], XGBoost [89], and SVM [90]. All comparative models follow the same structure, as outlined in prior research.…”
Section: Resultsmentioning
confidence: 99%
“…According to the result shown in Table 11, the proposed model not only surpasses all benchmark models but also outperforms all other comparative models in all three measures (i.e., MAPE, RMSE, and MAE) The comparative performance between the proposed model and prior studies is shown in Table 11. This comparative analysis is conducted with the other models that appear in the literature such as benchmark model 1 [53], LSTM [88], XGBoost [89], and SVM [90]. All comparative models follow the same structure, as outlined in prior research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Support vector machine (SVM) is a supervised machine learning that can deal with classification and regression problems (36), the basic idea is to find the optimal classification hyperplane that completely separates the two classes of samples in the original space in the linearly divisible case and to use kernel methods in the nonlinear case to solve problems that are nonlinear in low-dimensional space as linearly integrable problems in high-dimensional space (37). Delineating the hyperplane can be defined as a linear equation:…”
Section: Support Vector Machinementioning
confidence: 99%
“…Several works have evaluated electric appliance ownership and electricity consumption, and some generated load profiles, for Thai residents. However, they often do not differentiate between urban and rural residents [25][26][27][28], focus solely on urban households [29,30], industries [31], educational institutes [32,33] or the whole country [34], were conducted with a small sample size [7,14,[35][36][37], or a combination of all of the above. Thus, we aim to close this gap and apparent research need in the following sections.…”
Section: Evaluation and Generation Of The Energy Demandmentioning
confidence: 99%